Framework for the Opioid Use Disorder Cascade of Care: Adaptation and Application for a Large Municipal Health System - Mariah M. Kalmin; Christina Crowley; Lia Pak; Colleen M. McCullough; Beth Ann Griffin; Kyle Ragins; Hrishikesh Belani; Katherine E. Watkins (Public Health Reports®, 2026)
Objectives: Most people with opioid use disorder (OUD) do not receive effective treatments despite their existence. The OUD cascade of care framework can be used to inform quality improvement efforts to address this gap, but data access and linkage requirements may limit its use. We sought to adapt the framework under the constraints of electronic health record data and identify patient populations at risk for OUD treatment discontinuity. Materials and Methods: We extracted data on patients with OUD from the Los Angeles County Department of Health Services from July 2022 through June 2023. We adapted the cascade of care to include probable OUD diagnosis, receipt of naloxone prescription, and receipt of ≥1 and ≥2 buprenorphine prescriptions. We then stratified and conducted statistical analyses for associations by sex, race and ethnicity, and facility type (inpatient, primary care, emergency, or urgent care). Results: Of 3881 patients identified with probable OUD, 49% received a naloxone prescription and 30% and 17% had ≥1 and ≥2 buprenorphine prescriptions, respectively, in 1 year. Non-Hispanic Black and Hispanic patients were less likely to receive buprenorphine prescriptions than were non-Hispanic White patients and patients of other or unknown race and ethnicity. We observed larger gaps in care between receipt of ≥1 and ≥2 buprenorphine prescriptions for patients using urgent care and emergency departments compared with patients in other settings. Practice Implications: This study illustrates substantial gaps between OUD diagnosis and treatment. This adapted framework for the OUD cascade of care can serve as a quality-monitoring tool to aid clinicians and health care administrators in narrowing the treatment gap for people with OUD.